Improving test performance of students with disabilities... on district and state assessments - Elliott, Judy L. 4 0 16; Thurlow, Martha L.; 5 (Thousand Oaks, California : Corwin Press, 2006)
Presents a guide for teachers in helping students with disabilities achieve success on district and state tests, providing information on accountability, testing, parent support, and more.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Education;Ability testing;Education;Ability;Testing.;Government policy -- Educational tests and measurements;Children with disabilities;Education and state;Educational tests and measurements;Handicapped children;Education -- United States.;United States.;United States.;United States.;United States;United States; 20; 2